The Influence of Bi Rate to the Distribution of Working Capital Loans - Kurnianingrum, Dian (Binus Business Review, 2015)
This research âThe influence of BI rate to the distribution of working capital loans" is conducted atÂ Indonesian commercial bank during the month of January 2005 until May 2009. The purpose of this research isÂ to determine the effect of BI rate toward the distribution of working capital loans. To test the researchÂ hypotheses, the data were analyzed by using Pearson correlate and simple linear regression. Based on research,Â BI rate significantly influence the distribution of working capital loans. BI rate gives a negative impact to theÂ distribution of working capital loans. It means, the increase in BI rate will decrease the distribution of workingÂ capital loans, and vice versa, the decrease in BI rate will increase the distribution of working capital loans.